Acupuncture Improves Heart Rate Variability, Oxidative Stress Level, Exercise Tolerance, and Quality of Life in Tracheal Collapse Dogs - Phurion Chueainta; Veerasak Punyapornwithaya; Weerapongse Tangjitjaroen; Wanpitak Pongkan; Chavalit Boonyapakorn (Veterinary Sciences, 2022)
Among the respiratory disorders in dogs from small breeds, tracheal collapse is one of the most commonly found in clinical practice. Presently, acupuncture is widely used as an alternative treatment which was shown to bring about positive effects in the treatment of human respiratory diseases. The present study demonstrated the effect of acupuncture on tracheal collapse dogs. We hypothesized that acupuncture can help dogs suffering from tracheal collapse by improving various parameters including heart rate variability, serum biomarkers for oxidative stress, exercise performance, and quality of life. Twenty client-owned dogs from small breeds with tracheal collapse disease were enrolled. The study was divided into two 5-week periods. During the first period, the dogs received normal veterinary care but received no acupuncture treatment (NAC). After completing that period, all forms of treatment were withheld for one week before the beginning of the second period. In the second period, all dogs restarted normal veterinary care and underwent acupuncture treatment (AC) once a week for five consecutive weeks. Blood was collected at the beginning and end of each of the two periods for malondialdehyde (MDA) level measurement. Heart rate variability (HRV) was recorded at the 1st, 3rd and 5th weeks of both periods. Exercise tests were performed at the beginning and end of AC period and questionnaire interviews with the owners were accomplished at the end of each period. The results showed that acupuncture can alleviate clinical signs of tracheal collapse, reduce MDA level, and improve sympathovagal balance. We suggest that acupuncture treatment could be used as an adjunct treatment for canine tracheal collapse.